Employee retention in call centre industry - Sa'ad, Shukriwani (2012)
Employee retention is a challenge in many organizations. Demographical and economic change have created a more confident and demanding employee, which makes it necessary for organizations to be competitive and work harder at meeting employees needs in order to retain their loyalty. The purpose of this study was to indentify the factors that impact employee retention in call centre organization. The literature review that framed of this study focused on employee retention, learning and working climate. The study was conducted using a set of questionnaire as the primary data to gathering strategy and recommendations were made based on the data that collected according to the topics reviewed in the literature section. From the study, learning does have no any relationship to intention to stay or employee retention in call centre. The selected demographic variables namely age, tenure and level of education also does have no relationship into employee retention in call centre. However, the variables under working climate namely pressure of work and following procedures has significant impact to employee retention in call centre.